Quality of kids' meals in fast-food restaurants: the nutritional content is not enough for an informed choice - Pinto, DC (2021)
Objective Eating out in restaurants is a common family behavior, but it has been persistently associated with unbalanced nutrient intakes, contributing to create and reinforce unhealthy food habits among children. The purpose of this study was to evaluate the kids' meals from three common well-known restaurant chains in Portugal. Methods The nutritional composition (total fat, carbohydrates, protein, and sodium content) of the menus was analyzed bromatologicaly, and food portions were also examined. The assessment was carried out according to the European Food Safety Authority recommendations. Results Analyses of the menus from the two points of view revealed that the evaluations for macronutrients and food portions may return contradictory results. Protein, carbohydrates, and fats are compliant with the requirements for most of the meals. The analysis from the food portion perspective exceeds the requirements for the meat, fish, and eggs groups, as well as for fats and oils. Fruits, vegetables, and pulses are not present in the menus. Despite the balance associated with the macronutrients, the salt content exceeds the recommendations for most of the meals. Conclusion Popular fast-food chain restaurants have already adapted to comply with nutritional recommendations, whilst neglecting important recommended foods such as fruit, pulses, and vegetables. This study points not only to the need of investing in the improvement of the offerings, but also to the importance of fighting the tendency to reduce the perception of food quality to its nutritional content, leading consumers to believe that the meals offered are balanced when they are not.